2017
DOI: 10.1007/s11284-017-1466-z
|View full text |Cite|
|
Sign up to set email alerts
|

Web image search revealed large‐scale variations in breeding season and nuptial coloration in a mutually ornamented fish, Tribolodon hakonensis

Abstract: Geographic variations in reproductive traits are important for evolutionary biology, but often difficult to investigate because of the need for a large‐scale survey and the ephemeral nature of secondary sexual characteristics. Here, using web image searches (Google Images and Twitter), we revealed large‐scale geographic variations (>1500 km) in breeding timing and nuptial coloration in the mutually ornamented fish, Japanese dace (Tribolodon hakonensis). As this fish is easily caught and many anglers upload the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Th shows greater variation in nuptial coloration patterns in regions where it is allopatric with its hybridizing species (i.e. Ts and T. brandtii) than in regions where it is sympatric with those species (Atsumi and Koizumi 2017b). If the nuptial coloration of Th contributes to sexual isolation as suggested by the present study, selection against hybridization should favor species-specific color patterns in sympatric regions, thereby reducing the variation in nuptial coloration of Th in those regions.…”
Section: Discussionmentioning
confidence: 48%
“…Th shows greater variation in nuptial coloration patterns in regions where it is allopatric with its hybridizing species (i.e. Ts and T. brandtii) than in regions where it is sympatric with those species (Atsumi and Koizumi 2017b). If the nuptial coloration of Th contributes to sexual isolation as suggested by the present study, selection against hybridization should favor species-specific color patterns in sympatric regions, thereby reducing the variation in nuptial coloration of Th in those regions.…”
Section: Discussionmentioning
confidence: 48%
“…1a). We compared the breeding color patterns of the T. hakonensis specimens in the present study (n = 191) with those described by Atsumi and Koizumi (2017), and found that the former matched those of populations in the Tama, Chikuma (Nagano), and Chitose (Hokkaido) Rivers [Fig. 2b, d in Atsumi and Koizumi (2017)].…”
Section: Possible Hybrids Of Tribolodon In the Tama Rivermentioning
confidence: 55%
“…The specimens were examined using two morphological keys, the cephalic lateral line system and breeding color, which have been used to identify T. hakonensis and T. brandtii previously (Sakai 1995;Sakai and Amano 2014;Atsumi and Koizumi 2017). T. brandtii maruta can be distinguished from T. hakonensis by the connection of the preoperculo-mandibular canal of the cephalic lateral line system to the postocular commissure (Sakai and Amano 2014); the presence or absence of this connection can be observed in fish larger than 80 mm SL (Kurawaka 1977).…”
Section: Morphological Analysismentioning
confidence: 99%
“…Brightly colored body areas (zones) predetermine sexual behavior and mate choice [ 43 ] and are primally located on the lateral side of fish. In other fish species, similar zones with similar functional significance can be distinguished [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%